HISTORICAL AND PEDAGOGICAL ANALYSIS OF THE FORMATION AND DEVELOPMENT OF PEDAGOGY OF LABOR IN POLAND - Kohut, Svitlana (Continuing Professional Education: Theory and Practice, 2019)
Under the conditions of unitary educational space creation, and different scientific views on the formation of continuous professional education “returning to sources” – studying peculiarities of the development of pedagogy of labor as a theoretical base of professional education – is of great significance. Polish scientists made a considerable theoretical and practical contribution into the development of pedagogy of labor. The author considers historical and pedagogical preconditions of the latter as a scientific sub discipline in Poland. The author also analyzes pedagogical views of Polish pedagogues on labor, as well as the views of scientists of different historical periods who were creating sources of pedagogy of labor and had a direct influence on its basement creation and development. A special attention is paid to Tadeusz Wacław Nowacki’s scientific work, the founder of theoretical and methodological principles of pedagogy of labor. It is mentionedin theconclusion that modern understanding of labor and its formation as a specific pedagogical sub discipline was developing during some thematic stages – from the stage of the reflection on labor value to the stage of the institutional organization of professional education. As a result the question of the methodic support of training professionals to teach in different professional institutions of education was raised. It is also stressed on the value of research results of pedagogy of labor in the light of changes in understanding its meaning not only for the Polishprofessional education environment but for the formation of a unitary educational space of qualified professionals’ training under the conditions of globalized labor market.